Transcription of cloned Moloney murine leukemia proviral DNA injected into Xenopus laevis oocytes. - Breindl, M (1983)
We have microinjected genomic DNA clones containing the Moloney murine leukemia virus (M-MuLV) proviral genome and flanking mouse sequences from Mov-3, Mov-7 and Mov-10 mice into Xenopus laevis oocytes and analyzed the virus-specific transcription and translation products. These mouse strains carry a proviral genome copy of M-MuLV in their germ line at different chromosomal positions and differ from each other with respect to expression of the proviral genome. We show here that the different M-MuLV proviral genome copies were transcribed into virus-specific RNA with similar efficiencies. Transcription of viral RNA initiated correctly at the viral promoter in the 5' LTR, whereas the promoter in the 3' LTR was used with a much lower frequency, if at all, for initiation of RNA synthesis. Most of the virus-specific transcripts were smaller than authentic M-MuLV mRNA and confined to the oocyte nucleus. Using immunoprecipitation, we were not able to detect virus-specific proteins after injection of proviral DNA, whereas after injection of a comparable amount of M-MuLV mRNA viral protein was readily detectable.